Systematic Literatur : Metode dan Model Pembelajaran Matematika di Tingkat Sekolah Menengah - Nuralia Nuralia; Rini Khomsatun; Silvani Rahmawati; Rena Revita (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This study aims to examine the effectiveness of various innovative learning models on improving student learning outcomes and mathematical skills at the junior high school and senior high school levels. The method used is a literarure study of previous research results that applied learning models such as the Flipped Classroom, Project-Based Learning (PjBL), Peer-Led Team Learning (PLTL), Discovery Learning, Mind Mapping, and other cooperative learning models. The analysis results indicate that these models generally have a positive impact on enhancing students' learning engagement, critical and creative thinking skills, numeracy skills, mathematical communication, and problem-solving abilities. These findings reinforce the urgency of adopting student-centred learning approaches based on higher-order thinking skills (HOTS). Therefore, it is recommended that teachers continue to develop the application of innovative learning models in accordance with the characteristics of students and supported by educational policies that encourage innovation and continuous training. This research is expected to serve as a reference for educators and policymakers in designing more effective and meaningful learning.